TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS IN CHILDCARE CENTERS (TASKA): A RESEARCH COMPARING TEACHING AND LEARNING IN TASKA WITH MODERN PARENT PERSPECTIVE - ALYA QISTINA ALIAS; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study explores teaching approaches in Malaysian childcare centres (TASKA) and compares them with modern parental expectations. TASKA mainly uses play-based learning, motor skill development, language enhancement, and value-based activities, promoting holistic growth. Teachers find play-based methods effective but face challenges like limited resources and diverse children’s behaviors. Parents prioritize safety, moral education, communication skills, and early technology exposure. While TASK meets most expectations, there is a gap in incorporating modern digital learning tools to equip children with 21st-century skills. The study recommends improving teacher training, strengthening parent collaboration, and introducing innovative, age-appropriate technology in early education.